2013
DOI: 10.1590/0102-311x00150012
|View full text |Cite
|
Sign up to set email alerts
|

Poluição do ar e doenças respiratórias e cardiovasculares: estudo de séries temporais em Cubatão, São Paulo, Brasil

Abstract: This study evaluated the association between air pollution and hospital admissions due to respiratory and cardiovascular diseases in Cubatão, São Paulo State, Brazil. Generalized additive Poisson regression models were used to model daily concentrations of particulate matter (PM10), sulfur dioxide (SO2), and ozone (O3) and daily hospital admissions counts. Explanatory variables were temperature, relative humidity, day of the week, and holidays. For each increment of 10µg/m³ in PM10, we found an excess of 4.25 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 12 publications
1
10
0
9
Order By: Relevance
“…, 4 , 24 However, the fine (PM 2.5 ) particulate is scarcely studied, as it is not quantified by the environmental agency stations; recently, national studies were published demonstrating the role of this fraction in the genesis of hospital admissions for respiratory diseases 1011 , 19 In Taubaté, the RRs of hospitalizations for pneumonia and asthma ranged between 4.1% and 6.3%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 4 , 24 However, the fine (PM 2.5 ) particulate is scarcely studied, as it is not quantified by the environmental agency stations; recently, national studies were published demonstrating the role of this fraction in the genesis of hospital admissions for respiratory diseases 1011 , 19 In Taubaté, the RRs of hospitalizations for pneumonia and asthma ranged between 4.1% and 6.3%.…”
Section: Discussionmentioning
confidence: 99%
“…, 4 , 24 No entanto, o particulado fino PM 2.5 é pouco estudado pelo fato de as estações das agências ambientais não o quantificarem; recentemente, foram publicados artigos nacionais que mostraram o papel dessa fração na gênese das internações por doenças respiratórias 1011 , 19 Em Taubaté, os riscos relativos para internações por pneumonias e asma variaram entre 4,1% e 6,3%.…”
Section: Discussionunclassified
“…2,3 Studies in Brazil, both in large cities and in medium-sized cities, have shown that respiratory diseases other than pneumonia are noticeably influenced by the effects of exposure to air pollutants, such as particulate matter less than 10 microns in aerodynamic diameter (PM 10 ), nitrogen dioxide (NO 2 ), sulfur dioxide (SO 2 ), ozone (O 3 ) and carbon monoxide (CO), thereby leading to hospitalizations. [4][5][6][7][8] These pollutants are usually quantified through monitoring which the first level is from ground level to 40 meters above the ground, and this method has already been validate. 10 Fine particulate matter (PM 2.5 ), which accounts for 60 to 70% of PM 10 , 11 along with carbon monoxide (CO), nitrogen oxides, ozone and volatile organic compounds (VOCs), are the pollutants for which concentrations are estimated through the model.…”
Section: Introductionmentioning
confidence: 99%
“…Além disso, a alta concentração do tráfego de veículos num espaço cada vez mais limitado e o aumento progressivo do parque industrial nas grandes cidades expõem grande parcela da população, diariamente, à emissão de poluentes liberados tanto por veículos automotores quanto pelas chaminés das indústrias (Paes et al, 2006). Apesar dos esforços empreendidos e da redução sistemática da emissão de poluentes nas últimas décadas, os padrões de qualidade do ar são, frequentemente, ultrapassados e, com isso, vários programas governamentais em todo o mundo têm sido desenvolvidos no sentido de analisar e minimizar o impacto da poluição sobre a saúde humana, mas, apesar dos notáveis avanços obtidos nas últimas décadas em direção a um ambiente com ar mais limpo, os atuais níveis de poluição experimentados pela maior parcela da população humana continuam a se mostrar bastante danosos à saúde (Gouveia et al, 2006;Nardocci et al, 2013). A elevação da concentração populacional, do desenvolvimento industrial e do aumento da frota veicular contribui para o aumento da poluição atmosférica, afetando a todos de uma maneira geral, porém, a população de baixa renda é ainda mais vulnerável às mazelas do ar poluído 1 Introdução 5 nas grandes cidades, uma vez que a má alimentação, a exposição a ambientes insalubres, a precariedade das moradias, a falta de infraestrutura urbana básica e de saúde, o subemprego, entre outros aspectos, são condições agravantes para o desenvolvimento de doenças associadas à poluição (Freitas et al, 2004;Cançado et al, 2006;Danni-Oliveira et al;Tresmondi et al, 2008).…”
Section: Introductionunclassified
“…Vários estudos têm demonstrado a associação entre níveis diários de diversos poluentes e uma série de efeitos deletérios à saúde, que vão desde as malformações congênitas ou menor ganho de peso durante a gestação, passando por adoecimentos por causas específicas ligadas, principalmente, ao trato respiratório e cardiovascular e, finalmente, um aumento na mortalidade total na população (Gouveia et al, 2006). Estudos de séries temporais realizados em Cubatão encontraram associação significativa entre as concentrações no ar de material particulado (PM 10 ) e o total de internações por doenças respiratórias, e doenças cardiovasculares em adultos (Nardocci et al, 2013). Outros estudos têm sido desenvolvidos no sentido de se demonstrar a consistente associação entre a poluição do ar e o aumento do risco de doenças cardiovasculares, não somente pelo aumento no número de mortes, mas também pela maior ocorrência de infarto agudo do miocárdio, de arritmias complexas e redução da variabilidade da frequência cardíaca, este último considerado um indicador de risco para morte súbita.…”
Section: Introductionunclassified